Insurance Type Influences Access to Biologics and Healthcare Utilization in Pediatric Crohn's Disease. Issue 3 (7th August 2021) - Quiros, Jose Antonio; Andrews, Annie Lintzenich; Brinton, Daniel; Simpson, Kit; Simpson, Annie
Abstract: Background: The objective of this study is to determine if there is an association between insurance status and access to biologics among children with Crohn's disease (CD). Additionally, we seek to determine differences in healthcare utilization between these groups, utilizing a national sample of children with CD. Methods: Children aged 8–18 with a diagnosis of CD were identified from 2012–2016 Truven Health MarketScan (IBM Watson Health). Patients were classified into Public/Medicaid or as Commercial/Privately Insured. Descriptive statistics were compared between groups and sensitivity analysis performed using inverse probability of treatment weighting. Adjusted differences in healthcare utilization were estimated by multiple linear regression models. Results: We identified 6163 patients with a diagnosis of CD. There were no significant differences in each payer group's demographic characteristics, comorbidities, or surgery rates. Over the 18-month follow-up period, 132 (20.4%) subjects in the public insurance group and 851 (15.4%) children in the private insurance group received biologics. Medicaid patients were 39% more likely to receive a biologic agent within 18 months of diagnosis compared to privately insured children ( P = .0004). Postdiagnosis rates of hospitalizations and Emergency Department visits were significantly higher for the Medicaid group. Conclusions: In this national sample of children with CD, publicly insured children were more likely to receive a biologic within 18 months of diagnosis compared to children with private insurance. At all points in time, publicly insured children also utilized emergency room services and required hospitalization at a significantly higher rate. Lay Summary: This is a comparison of commercially and Medicaid insured children with Crohn's disease. Children covered by Medicaid were more likely to go on a biologic agent, had higher rates of hospitalization and emergency room care. Potential causes and implications are discussed.